A Memristor‐Based Bioinspired Multimodal Sensory Memory System for Sensory Adaptation of Robots. (1st May 2022) - Pan, Xinqiang; Wang, Jiejun; Deng, Zhen; Shuai, Yao; Luo, Wenbo; Luo, Wen; Xie, Qin; Xiao, Yao; Tang, Song; Jiang, Shuwen; Wu, Chuangui; Zhu, Feng; et al.
Abstract : Sensory adaptation plays a critical role in humans interacting with the environment. Inspired by humans, realization of sensory adaptation on robots can make them adapt to the environment gradually. The gradual change of sensitivity that depends on recent experience of external stimuli is the most important process for the adaptation. To realize sensory adaptation, such change of sensitivity needs to be realized. It is proposed to fabricate the memristor based on single‐crystalline LiNbO3 thin film. The resistance of the memristor can be changed monotonically and gradually with the increase in the number of voltage pulses, which can be ascribed to the property of single‐crystalline thin films. Based on the characteristic, it is proposed to use the memristor as artificial synapse of the proposed bioinspired system, using conductance of the memristor to denote susceptibility value to realize the gradual change of sensitivity by recent external stimuli. A novel general excitation method of signals from multimodal sensors on memristor is proposed and utilized in the signal‐coupling module of the system, which makes the system realize sensory adaptation for different stimuli accepted by multimodal sensors. Using artificial sensory memory systems, sensory adaptation on robot is realized for the first time herein. Abstract : With the characteristics of the memristor based on single‐crystalline thin film, the memristor is used as an artificial synapse in sensory memory systems. The conductance of the memristor is used to denote the susceptibility value to realize the key changing process of sensitivity caused by external stimuli (sensor accepted) in sensory adaptation. Sensory adaptation of robot is demonstrated with the system.